2020
DOI: 10.1177/0193945920932290
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Predicts Psycho-behavioral Improvement after Breast Cancer Diagnosis: Influence of Childhood Adversity

Abstract: Mindfulness-based interventions provide psychological benefit after breast cancer diagnosis. The aims of this study were to determine whether within-person change in facets of mindfulness predict psycho-behavioral improvements in women with breast cancer, and to assess the influence of childhood adversity on those improvements. Women randomized to the mindfulness arm of a larger trial were evaluated. Psychometric instruments and the Five Facets of Mindfulness Questionnaire were completed pre-, mid-, at complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It was also found that the differences in psychological well-being between people who had been exposed to ACEs compared to those who had not were similar during the diagnostic and the treatment phase [21]. Additionally, one study found that people with ACEs experienced less social and professional support during cancer treatment [35] and another study [33] showed that they may profit from mindfulness-based therapy.…”
Section: Other Psychological Variables and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that the differences in psychological well-being between people who had been exposed to ACEs compared to those who had not were similar during the diagnostic and the treatment phase [21]. Additionally, one study found that people with ACEs experienced less social and professional support during cancer treatment [35] and another study [33] showed that they may profit from mindfulness-based therapy.…”
Section: Other Psychological Variables and Mechanismsmentioning
confidence: 99%
“…The majority of the 25 studies were conducted in the USA (n = 19, 76.0%) (see Table 2) [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The other studies were conducted in the UK [34,35], Brazil [36], Turkey [37],…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Others have shown that practicing mindfulness improves the immune response to psychological stress, lowering the production of proinflammatory cytokines. 34…”
Section: Mechanisms Of Mindfulnessmentioning
confidence: 99%
“…We have shown in two dismantling trials that acceptance is a key component of MBIs for targeting stress perceptions and biology ( Lindsay et al., 2018 ; Chin et al., 2019a ). Moreover, MBIs have been uniquely effective for reducing mental health symptoms among adults with a history of childhood maltreatment ( Earley et al., 2014 ; Joss et al., 2019 ; Kimbrough et al., 2010 ; Kuyken et al., 2015 ; Ma and Teasdale, 2004 ; Williams et al., 2014 ; for a review, see Joss and Teicher, 2021 ) and experiential acceptance is thought to underlie improvements ( Thompson et al., 2011 ; Janusek et al., 2021 ). Whether these effects extend to markers of physical health remains unknown.…”
Section: What Are Mbis?mentioning
confidence: 99%